Pengaruh biaya produksi, biaya operasional, struktur modal, dan likuiditas terhadap profitabilitas - Afika Roichatul Jannah; Sulistyo; Doni Wirshandono Yogivaria (Jurnal Riset Mahasiswa Akuntansi, 2020)
The purpose of this study is to examine and analyze the Effect of Production Costs, Operational Costs, Capital Structure, and Liquidity on Profitability. 18 (eighteen) food and beverage sub sector manufacturing companies listed on the IDX became the population in this study, with 11 companies as samples. The sampling technique uses puposive sampling method. The data used are secondary data in the form of financial statements and annual food and beverage companies for the 2014-2017 period which can be accessed through www.idx.co.id. This study uses multiple linear regression analysis techniques, which previously tested classical assumptions and hypothesis testing using simultaneous tests (F test), partial tests (t test), and the coefficient of determination (R Square). The results of this study indicate that Production Costs, Operational Costs, Capital Structure, and Liquidity simultaneously affect Profitability. And partially only Operating Costs that affect Profitability, while Production Costs, Capital Structure, and Liquidity do not affect partially Profitability.